PENYELENGGARAAN TATA NASKAH DINAS DI LINGKUNGAN PEMERINTAH KECAMATAN - Fitriani, Aida (Universitas Kapuas Sintang, 2024)
The Sintang District Government along with the Village Government and Village Government in Sintang District face several problems, especially in the field of official manuscripts. Indications of this can be seen from the way official manuscripts are typed, the use of headers, the installation of signboards, both the District Government and the Village Government and Village Government, have not fully referred to the Sintang Regent Regulation Number 22 of 2006 concerning Guidelines for Official Manuscripts within the Sintang Regency Government.